Formation of an Inhibitor against Factor VIII as a Postoperative Complication in a Severe Case of Hemophilia A - Beck, E; Bachmann, F; Müller, J; Duckert, F (Thrombosis and Haemostasis, 1962)
A case of haemophilia A with formation of an inhibitor after transfusions as a postoperative complication is described. The inhibitor was active against factor VIII from human, bovine and porcine source. It corresponds to the progressively active type of inhibitor.The necessity of a complete examination including incubation tests before operations and before the use of concentrated AHG on hemophiliacs is stressed. In the presence of an inhibitor of this type animal AHG should not be infused, because it will be inactivated as well as human AHG and provokes an additive species specific sensibilization.